Influências cruzadas na constituição e na expansão do sistema de pós-graduação stricto sensu em educação no Brasil - Menga Lüdke (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
This text deals with the principal influences suffered, at their outset, by Masters and Doctoral Programmes in Brazil, based on models already well developed in the period 1960/70, by countries like France and the USA. As I had the opportunity to live in these countries as a postgraduate student, from where I returned to Brazil when the first programmes were being implanted, I was able to confer such influences and their results. This is clearly a personal view, limited by my own experience, and not furthered by means of a study or more careful analysis. However, I was able to confront and confirm my impressions with those of colleagues who lived similar experiences but nevertheless I accept total responsibility for the interpretations which I present in the text as suggestions for other interpretations and studies which may further the suppositions which I have managed to raise.